Significance of Lymph Node Metastasis in Resectable Well-differentiated Pancreatic Neuroendocrine Tumor. Issue 7 (August 2019) - Harimoto, Norifumi; Hoshino, Kouki; Muranushi, Ryo; Hagiwara, Kei; Yamanaka, Takahiro; Ishii, Norihiro; Tsukagoshi, Mariko; Igarashi, Takamichi; Tanaka, Hiroshi; Watanabe, Akira; Kubo, Norio; Araki, Kenichirou; et al.
Abstract : Objectives: Understanding the effect of lymph node metastasis (LNM) on prognosis in pancreatic neuroendocrine neoplasm is helpful for surgery and follow-up. In this study, we investigated the significance of LNM in well-differentiated pancreatic neuroendocrine tumors (PanNETs) according to the World Health Organization 2017 classification. Methods: We retrospectively collected data for 95 consecutive patients with PanNET who underwent pancreatic resection with curative intent between January 2008 and December 2017 at 6 institutions. The clinicopathological factors were compared in patients with and without LNM, and prognostic factors were analyzed. Results: Lymph node metastasis was significantly associated with malignant potential of PanNET, such as larger tumor size, higher Ki-67 index, higher tumor grade, and higher incidence of lymphatic, vessel, and neural invasion. Lymph node metastasis was also associated with disease-free but not overall survival. Multivariate analysis identified NET grade 2 (G2) and G3 as independent risk factors for recurrence after curative resection. Conclusions: World Health Organization 2017 classification was the most independent prognostic factor in patients with resectable well-differentiated PanNETs. Patients with G2 and higher-grade tumors require lymph node dissection to improve prognosis.